Relation Entre Les Facteurs Socio-Économiques Et L’anémie Au Cours De La Grossesse (Nouakchott – Mauritanie) - Sass, Setty; Mohamed, Mariem Sidi; Zein, Ahmed; Elberae, Ahmed; Khadmaoui, Abderrazzak; Khllayoun, Soad; Lrhorfi, L. Aicha; Bengueddour, Rachid (European Scientific Journal, ESJ, 2017)
Anemia is one of the most common public health problems in the world, especially among pregnant women. The objective of our study is to describe the socio-demographic and epidemiological profile of anemic women. We conducted a prospective study in the maternity department of the CHEIKH ZAYED Hospital Center in Nouakchott, during the period from 2015 to 2016. In addition, 400 pregnant women are interviewed, including 49.75% (n=199) with anemia, of which 34.17% were under 24 years of age, 63.31% are white Moors and 90.45% are at home. As a result, Statistical analyzes show a significant relationship, between certain socio-economic factors (Age, provenence area, ethnic origin, household size) and anemia.